The Effectiveness of Audiovisual Education on Teenager' Knowledge Levels About the Menstrual Cycle - Dwie Suci Wahyuni; Vella Yovinna Tobing; Riau Roslita (HealthCare Nursing Journal, 2023)
Changes in the menstrual cycle during adolescence can be an indication of reproductive health problems. Knowing whether or not the menstrual cycle is normal will help detect reproductive health problems in the early stages; therefore, sufficient knowledge regarding the menstrual cycle is needed. It is believed that providing education will be more effective using audiovisual media as the five senses channel the needed knowledge to the brain as much as 75%-87%, while the sense of sight is only 13%-25%. The purpose of this study was to identify the effectiveness of audiovisual education on the level of knowledge of adolescents about the menstrual cycle. This research was conducted at State Junior High School (SMP) 20 Pekanbaru with the type of pre-experimental research using pre-test and post-test without a control group design. A total of 30 respondents took part in this study selected using the non-probability sampling technique, specifically the consecutive sampling technique. The analysis used was univariate analysis using frequency distribution and bivariate analysis using paired t-test. The results showed that respondents were between 14-16 years old with the average age of first menstruation being 12 years old; the distribution of respondents who had not received information on how to calculate the menstrual cycle was as many as 18 respondents (60.0%), while 16 respondents (53.3%) had not asked about this issue to their parents. The results of the majority of adolescent knowledge levels at the time of the pre-test were in the ‘poor category’ (63.3%), while after being provided with education using audiovisual post-test values, the majority of respondents were in the ‘good category’ (93.3%). The result of the paired T-tes obtained a P value of 0,001. This study recommends that schools and parents should provide education to female students about the menstrual cycle.